How do trees survive a cyclone? The relative role of individual and site characteristics over mortality. (22nd July 2021) - Liebsch, Dieter; Marcilio‐Silva, Vinicius; Marcon, Amanda K.; GalvÃo, Franklin; Mikich, Sandra Bos; Marques, MÁrcia Cristina Mendes
Abstract: Cyclones are an increasing disturbance in the subtropical region of South America, but their impacts over the forests are still poorly documented. Here, we evaluate the effects of an extratropical cyclone over tree mortality in Araucaria Forest remnants in southern Brazil. We surveyed 116 sites (10 × 20 m each) and collected data on all tree individuals presenting DBH ≥ 4.8 cm before (2009) and after (2014) the occurrence of an extratropical cyclone. Using GLM models, we checked how the cyclone occurrence, different plant traits (DBH, trunk branching, wood density, successional group and evolutionary distinctiveness) and site characteristics (basal area, exposure, landscape protection, nearest border distance, cyclone border distance and the presence of native bamboo species) could impact tree mortality. The GLM model selection shows that the lowest AIC model considers all predictors separately and their interaction with the cyclone. The results showed that the cyclone occurrence and some site characteristics (bamboo presence, site exposure, landscape protection, nearest border distance and cyclone border distance) and plant traits (successional group and evolutionary distinctiveness) are related to tree mortality. The intense deforestation and fragmentation of the Araucaria Forest coupled with the increase in cyclone frequency expected for the region due to climate change may increase mortality rates of these forests, affecting their resilience and phylogenetic structure. Further biodiversity conservation efforts in the Araucaria Forest need to consider the characteristics of sites for enabling the protection of forest remnants in areas under different exposures to cyclone impacts.